Pengaruh Perputaran Modal Kerja, Likuiditas Dan Struktur Modal Terhadap Profitabilitas Pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Siti Nadziroh; Agustina Widodo (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The aim of this research is to investigate the profitability of food and beverrage subsector manufacturing companies listed on the indonesia stock exchange from 2018 to 2022. This study was conducted by taking 16 sample sompanies using the purposive sampling method. The analysis method uses multiple linear regression analysis. This study shows that working capital turnover has an insignificant positive effect on profitability, liquidity has an insignificant positive effect on profitability and capital structure has a significant negative effect on profitability.